Homoeosis, canalization, decanalization, ‘characters’ and angiosperm origins - Mabberley, D. J.; Hay, A. (Edinburgh Journal of Botany, 2010)
Reproductive structure is considered in the context of process morphology: the significance of homoeotic transformations is commented on in Araceae and other modern angiosperms. Disruption leads to the rearrangement of processes and destabilization of process combinations, or decanalization. This is apparently more readily achieved in certain extant angiosperms than in others; both environmentally triggered decanalization, including galling, and genetically prompted decanalization are discussed and illustrated with examples including those leading to the expression of ‘lost’ features. This is extended to a consideration of ‘character’ comparisons in extant angiosperms and possible pitfalls there. Finally, this approach is applied to the relationship of certain extant groups of seed-plants and their fossil allies and it is concluded that modem ones are (distantly) interrelated relics of a complex of ‘hemiangiosperms’ of the Triassic.